Workplace diversity in female-dominated industries and intraindividual identity conflict - Magdalena Calderón-Orellana; Raúl Berríos (PLoS ONE, 2025)
This research paper examines the impact of gender and socioeconomic status (SES) diversity on intraindividual identity conflict within a female-dominated economic sector. The study also evaluates whether this relationship is moderated by gender and SES, as suggested in prior research. A quasi-experimental design was employed with 186 child protection workers as participants. Using vignettes that depicted varying levels of diversity, participants were randomly assigned to different conditions. The degree of dissimilarity was determined by comparing the diversity level described in the vignette with the participants’ individual characteristics, and intraindividual identity conflict was subsequently measured. Findings revealed that SES dissimilarity within a workgroup is associated with heightened intraindividual identity conflict. Furthermore, the study confirmed that SES moderates the relationship between diversity and intraindividual identity conflict. This research contributes to the existing body of knowledge on the effects of diversity on group identity conflicts, with a particular focus on intraindividual conflict in feminized occupations. Additionally, the findings on SES diversity underscore the importance of advancing our understanding of socioeconomic or class diversity and expanding the study of diversity beyond the Global North—topics that have been largely overlooked in the literature.